Transfection of Capsaspora owczarzaki, a close unicellular relative of animals - Parra Acero, Helena (2018)
How animals emerged from their unicellular ancestor remains a major evolutionary question. New genome data from the closest unicellular relatives of animals have provided important insights into the evolution of animal multicellularity. We know that the unicellular ancestor of animals had an unexpectedly complex genetic repertoire, including many genes that are key to animal development and multicellularity. Thus, assessing the function of these genes among unicellular relatives of animals is key to understanding how they were co-opted at the onset of the Metazoa. However, such analyses have been hampered by the lack of genetic tools. Progress has been made in choanoflagellates and teretosporeans, two of the three lineages closely related to animals, whereas no tools are yet available for functional analysis in the third lineage: the filastereans. Importantly, filastereans have a striking repertoire of genes involved in transcriptional regulation and other developmental processes. Here, we describe a reliable transfection method for the filasterean Capsaspora owczarzaki. We also provide a set of constructs for visualising subcellular structures in live cells. These tools convert Capsaspora into a unique experimentally tractable organism to use to investigate the origin and evolution of animal multicellularity.